2020
DOI: 10.3390/catal10030335
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reforming for Hydrogen Evolution: A Review

Abstract: Hydrogen is considered to be an ideal energy carrier to achieve low-carbon economy and sustainable energy supply. Production of hydrogen by catalytic reforming of organic compounds is one of the most important commercial processes. With the rapid development of photocatalysis in recent years, the applications of photocatalysis have been extended to the area of reforming hydrogen evolution. This research area has attracted extensive attention and exhibited potential for wide application in practice. Photocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 99 publications
1
29
0
1
Order By: Relevance
“…This rendered direct comparison of the catalytic properties of the bare TiO 2 materials impossible in this study. Otherwise, our hydrogen production results are of the same order as those in other works [ 13 , 57 , 58 , 59 ]. As can be seen from Figure 2 , the P25-based samples gave a higher H 2 production rate than the sol–gel-based samples, irrespectively if the Pt co-catalyst was formed by hydrogen reduction or calcination.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This rendered direct comparison of the catalytic properties of the bare TiO 2 materials impossible in this study. Otherwise, our hydrogen production results are of the same order as those in other works [ 13 , 57 , 58 , 59 ]. As can be seen from Figure 2 , the P25-based samples gave a higher H 2 production rate than the sol–gel-based samples, irrespectively if the Pt co-catalyst was formed by hydrogen reduction or calcination.…”
Section: Resultssupporting
confidence: 87%
“…Since hydrogen is regarded as an important secondary energy source for the future [ 3 , 4 , 5 ]; photocatalytic implementation of hydrogen production would give an opportunity to transform solar energy into chemical energy for storage [ 6 ]. Large numbers of publications have indicated that photoinduced reforming of alcohols such as methanol, glycerol and more, over semiconducting oxides in the presence of water, could be an efficient way of hydrogen generation [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Even if the conversion of the methanol in the photoinduced reforming reaction (1) is rather low compared to other methanol-reforming systems, reaction (1) is widely studied and used as a model reaction to compare photocatalysts [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are two types of sacrificial reagents: organic and inorganic based electron donors. Among organic electron donors, the most effective are water–alcohol mixtures, in particular, methanol > ethanol > ethylene glycol > glycerol [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. However, an increase in the concentration of the sacrificial agent does not always lead to an increase in the yield of hydrogen.…”
Section: The Utilization Of Photocatalysts Based On Tio mentioning
confidence: 99%
“…Effective photochemical biomass-to-hydrogen processes relying on solar energy inputs could valorize biomass feedstocks currently viewed as waste products, such as pulp generated during paper processing. Moreover, the possibility that this photochemical approach could also enable the production of low molecular weight aromatic products from the biomass stream concomitant with H 2 production could offer another economic advantage [ 2 ]. The targeted and currently unused biomass sources, such as raw lignocellulosic biomass, do present difficulties such as limited solubility and chemical inertness [ 63 ].…”
Section: Biomass-derived Substratesmentioning
confidence: 99%
“…The oxidation of H 2 coupled to the reduction of O 2 in a fuel cell produces water as the only product, a more environmentally friendly process than fossil fuel combustion, which produces harmful greenhouse gas emissions in the form of CO 2 . Moreover, hydrogen is also attractive as an alternative energy source because of its high energy density (e.g., 141.8 ⨯ 10 6 kJ/kg), which is greater than that of most fuels (e.g., 44 ⨯ 10 6 kJ/kg for gasoline) at room temperature [ 2 ]. The most prevalent production method for H 2 is steam reforming of methane feedstocks, producing nearly half of the hydrogen gas in the world [ 3 ].…”
Section: Introductionmentioning
confidence: 99%